ANALISIS NILAI-NILAI MOTIVASI BELAJAR PADA BUKU SISWA TEMA 4 KEWAJIBAN DAN HAKKU KELAS III MADRASAH IBTIDAIYAH TERBITAN KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN - Nurhasanah Fadhliana; Alfi Satria; Wiena Safitri (Bajang Institute, 2023)
This undergraduate thesis studied about the motivation values contained in Students’ Book Theme 4 “My Rights and Obligation” which can motivate the students in studying. The problem of this research started from if Students’ Book Theme 4 “My Rights and Obligation” Grade III Madrasah Ibtidaiyah Curriculum 2013 published by Ministry of Education and Culture has owned learning motivation values and how was the components’ quality of Students’ Book Theme 4 “My Rights and Obligation” can support students’ learning motivation. The purpose of this research was to find out learning motivation values and the components existed in Students’ Book Theme 4 “My Rights and Obligation” Grade III Curriculum 2013 which can make students’ improve their motivation in studying. This research employed library study approach with research type descriptive analysis and documentation technique. The collection of research data employed likert scale technique by giving points in the scoring sheet in accordance with the assessment criteria. The analysis result of students’ text book in this research showed that there have been motivation values in Students’ Book Theme 4 “My Rights and Obligation”, the motivation values existed in Students’ Book Theme 4 “My Rights and Obligation” Grade III were in the form of book components such as book picture illustration and sentences passage in the book material. The components in Students’ Book Theme 4 “My Rights and Obligation” which can increase students’ learning motivation also existed with percentage in the amount of 100% from the book size side, and included into excellent category, book design side in the amount of 74% included into excellent category, and book quality side obtained percentage 84,3% included into excellent category.